Assessment of Chicken Production Systems and Egg Quality Traits in and Around Borama District, Somaliland - Said, Naima Jama; Abdilahi, Abdi; Abdimahad, Kownin; Mahamed, Abdulahi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This study evaluated chicken production practices and egg quality traits among households in urban and rural villages of Borama District, Somaliland. A total of 131 respondents (67 urban and 64 rural) participated in the survey. The demographic profile showed a predominance of female respondents (84%) mostly aged between 31 and 40 years (62.6%). Significant differences were found in educational status, with higher illiteracy rates in rural areas (48.4%) compared to urban areas (14.4%) (p=0.000). Family size was significantly larger in rural villages (7.1 ± 0.17) than urban (6.4 ± 0.12) (p=0.002). The main purpose of keeping chickens was for sale (72.5%), followed by home consumption (20.6%). Hatching eggs for replacement was significantly higher in rural areas (75%) than urban (49.3%) (p=0.006). Feeding management showed significant differences between urban and rural settings (p=0.03). Most urban chicken keepers practiced scavenging with supplementation (97%), while a considerable proportion of rural respondents relied on scavenging only (37.5%). The primary feed sources included cereal grains and food leftovers, with cereal grains more common in rural areas (53.1%) than urban (28.4%) (p=0.000). Water was provided to most flocks (91.6%), but watering frequency and sources varied significantly (p=0.000). Urban chickens mostly had access to pipe water (68.7%), whereas rural chickens relied on pond and rainwater. Housing systems differed significantly (p=0.000), with traditional housing predominant in rural areas (92.2%) and more diverse systems including deep litter and backyard housing in urban villages. Newcastle disease was the most prevalent poultry disease (93.1%), and traditional control methods were widely used (38.2%). Predators (45%), flock mortality (20.6%), and diseases (14.5%) were major constraints affecting chicken production. Egg quality assessment revealed a significant difference in albumin height (p=0.04), with urban eggs having higher values. Other traits such as egg weight, yolk height, yolk weight, yolk color, albumin weight, and shell weight did not show significant variation between the two locations. The findings indicate the need to improve feeding practices, disease control, and housing conditions to enhance productivity and egg quality, especially in rural areas.